1994
DOI: 10.1139/b94-203
|View full text |Cite
|
Sign up to set email alerts
|

Colonization dynamics of algae in small artificial ponds

Abstract: WOOD, C.M. 1994. Colonization dynamics of algae in small artificial ponds. Can. J. Bot. 72: 1654-1665. The arrival, establishment, and growth of a variety of algae were studied in a series of newly established, small (48.5 L) artificial ponds located at three sites of differing characteristics in southern Ontario, Canada: open field, edge of woods, and deep woods. Algal colonization was most rapid at the open site, within 4 days of the ponds being filled, and was slowest at the deep woods site, presumably beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…This is in agreement with our earlier report observed in the same environment (Sekar et al, 1998(Sekar et al, , 2002. Initial dominance by unicellular organisms like Chlorella and cyanobacterial dominance during later stages have also been observed by other workers (Korte & Blinn, 1983;Williams et al, 1994). Pan & Lowe (1994) reported that the shift in prostate to erect diatoms in a stream, as observed in the present case, is a common phenomenon in periphyton succession in the absence of disturbance.…”
Section: Nutrient Dynamics and Succession In Biofilms 1899supporting
confidence: 94%
“…This is in agreement with our earlier report observed in the same environment (Sekar et al, 1998(Sekar et al, , 2002. Initial dominance by unicellular organisms like Chlorella and cyanobacterial dominance during later stages have also been observed by other workers (Korte & Blinn, 1983;Williams et al, 1994). Pan & Lowe (1994) reported that the shift in prostate to erect diatoms in a stream, as observed in the present case, is a common phenomenon in periphyton succession in the absence of disturbance.…”
Section: Nutrient Dynamics and Succession In Biofilms 1899supporting
confidence: 94%
“…Therefore, although we found low mosquito densities in pastureland containers in this study, other habitat types in pastureland, such as stock drinking troughs, may have lower average temperatures that can sustain larger immature mosquito populations . Containers in open sunlight may be particularly important mosquito habitat if they provide favourable temperatures for algae that provide food for mosquito larvae (Williams et al 1994). The results of this study also conflict with findings from a concurrent study in Waikanae and Paraparaumu using similar experimental containers but which were removed from the field and subsampled after homogenising their water (Leisnham et al 2004).…”
Section: Octcontrasting
confidence: 81%
“…Replacement of natural vegetation with agricultural crops has been shown to increase numbers of sunlit larval habitats, alter evapotranspiration rates and modify ambient air temperatures; all of which have been suggested to change the water temperatures of larval habitats and the abundance of immature mosquitoes (Walsh et al 1993;Lindblade et al 2000). Findings from other field studies have shown a direct association between water temperature and mosquito presence or abundance (e.g., Williams et al 1994;Sunish & Reuben 2001;Shililu et al 2003;Strickman & Kittayapong 2003). This is one of the first studies to quantify water temperature differences of mosquito larval habitats in urbanland, pastureland and native forest, and relate them to immature mosquito density.…”
Section: Octmentioning
confidence: 73%
See 1 more Smart Citation
“…The airborne microeukaryotes in the tap water containers were dominated, in terms of the number of species, by members of the Chlorophyta, which have been reported to dominate the airborne microorganisms of temperate regions (Brown et al 1964, Sharma et al 2007. Additionally, Chlorophytes are the first colonists in artificial ponds (Williams et al 1994), and they are considered as potential inocula for colonization of Antarctica as climate change continues to uncover new systems (Marshall & Chalmers 1997). In addition, Chrisostomou et al (2009) also observed high number of chlorophytes in a study of air-dispersed phytoplankton colonizing water containers in a rural area.…”
Section: Discussionmentioning
confidence: 99%